FACTORS THAT INFLUENCE THE CHOICE OF FAMILY PLANNING METHODS IN MARRIED MEN AGED 19-54 YEARS IN INDONESIA (FURTHER ANALYSIS OF 2017 THE DHS DATA) - Rahayu, Dian; Abdullah, Asnawi; Arlianti, Nopa (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Choosing a contraceptive methods for married men is very important to suppress the population explosion in Indonesia. Based on 2017 IDHS data, 7.5% of men used non-MKJP family planning methods. Meanwhile, Long Acting Contraceptive Methods (MKJP) is only 0.1%. The research aims to determine the factors that influence the choice of contraceptive methods for married men aged 19-54 years in Indonesia. Method: This research is an analytical survey conducted using secondary data from the 2017 SDKI with a cross-sectional design. The population in this study was all married men (PK) in Indonesia. The sampling design used in the 2017 IDHS is stratified sampling. In each district/city, several census blocks were selected using PPS (probability proportional sampling to size) with a total sample in this study of 765 respondents. Data analysis used multiple logistic regression tests with Stata 16. Results: the results showed that the selection of non-MKJP contraceptive methods was 98.09%. Meanwhile, MKJP for married men is only 1.91%. Multivariate test results show that contraceptive methods funded by insurance have the most dominant influence on the choice of contraceptives among married men in Indonesia (OR:53.57, 95%CI:13.40-214.19, p-value:0.0001). Recommendation: It is hoped that married men can increase awareness regarding participation as family planning acceptors.